Access to urban transportation system for individuals with disabilities. (July 2017) - Sze, N.N.; Christensen, Keith M.
Abstract: Urbanization and aging population has become a significant issue in many global cities. It is necessary that the design of built environment to be supportive and provide adequate access to essential urban and social resources, e.g. employment, education, medical, social welfare and recreation etc., for all, including individuals with disabilities. Safe, efficient and accessible transportation is a key component of community integration. This study attempts to review the current practices and guidelines for accessible design of transportation, both access to and within transport facilities, based on the information from the United States, United Kingdom, and Hong Kong. Besides, the effects of accessible design of transportation on perceived level of service, accessibility, safety and travel behavior would be examined. Therefore, good practices of accessible design that could address the needs for all, especially the elderly and individuals with different types of disability including visual impairment, hearing difficulty and reduced mobility, could be recommended. Hence, quality of life of vulnerable group can be enhanced, and community integration will be achieved in the long run. Highlights: Guidelines for accessible transport design in the US, UK and Hong Kong were reviewed. Efficient and safe maneuver of individual with different types of disability were considered. Perceived accessibility and safety was enhanced after the introduction of accessible design. Public transport use increased after the introduction of accessible design. Perceived quality of life was enhanced with the improvement of access to essential urban resources.